Valoração dos serviços ecossistêmicos em projetos de revitalização de brownfield: o caso da Brasital São Roque/SP - Kaam, Evandro Nogueira (2022)
Brownfields are still unknown in Brazil, although existing in several cities. In recent decades, the urban planning model of large centers has given rise to a process of building deindustrializations in the urban cenario, creating several idle and underutilized spaces, that over time have even became a source of social problems. Several countries have been developing environmental revitalization projects in brownfields, in order to bringing them back to the economic cycle using services based on nature (SBN). This model has gained space in discussions of sustainable urban planning as it allows manangers, companies and the community to actually increase the quality of life in cities, creating opportunities to invest and providing improvements in the menagement of public spaces. This study aims to conduct a servey of the infrastructure of a specific brownfield, applying SBN in its revitalization to clarify the potential for monetary valuation added to the Project. The brownfield located in the city of São Roque/SP – named Brasital – was the target of the study because it presents great potential of viability in the use of various ecosystem services (ES). The Brasital complex also features great spatial organization, open and wide environments, well lit and ventilated, characteristics that endorse the structural potential of the área. This study used a method for application and valuation of ecosystem services on Brasital Brownfield, measuring climate regulation, runoff reduction, air filtration and ventilation, carbono sequestration and recriation. Data measurement was based on the vegetation, water bodies and types of surfaces in the complex, except for the recriational service, which was measured through the number of residentes in the surroundings. The study presents approximately 22 million reais per year as a result of the ES application, but there is room for improvement in future studies if we consider in the methodology a more detailed analysis on the brownfield surroundings, and the methods to analyze types of vegetation, since that research admitted general data for calculations. This Project developed inclusive, sustainable and technological spaces, which are objectives of the 2030 Agenda. Such benefits brought by the use of ES – SBN – play a role in reducing difficulties to access infrastructure and urban services in cities, promoting climate improvements, reducing the vulnerability of these places, including natural desasters.